Las ciudades del deseo Las políticas de género, sexualidad y espacio urbano en el Caribe hispano - Valdez, Elena (Purdue University Press, 2023)
Las ciudades del deseo explores the representations of gender, sexuality, and urban space in contemporary narratives from Cuba, the Dominican Republic, and Puerto Rico. By examining a corpus of novels published since 2000, this book shows how the changes in urban landscape create a new image of the city that destroys traditional gender roles and produces different discourses on sexuality. At moments of crisis in political agendas that took place between 1990 and 2000, queer subjects became spokespeople outlining new national projects on each island, while claiming space in the national imaginary. The nation is no longer built on blood ties, patriarchal norms, or biological procreation, but rather starts incorporating previously excluded racial identities and sexual practices. By juxtaposing the narratives of the three countries and putting into dialogue the topics of nationality, sexuality, urban space, and sex tourism, Las ciudades del deseo breaks away from a tradition that tends to study them separately. The book contributes new perspectives on an emerging culture of resistance to heteronormative dynamics and power structures that is developing simultaneously in Cuba, Puerto Rico, and the Dominican Republic. It sheds light on larger connections between literature and LGBTQ activism in the Spanish-speaking Caribbean.Las ciudades del deseo explora las representaciones del género, la sexualidad y el espacio urbano en la narrativa contemporánea de Cuba, la República Dominicana y Puerto Rico. Aportando un análisis de varias novelas publicadas después de 2000, el libro muestra cómo los cambios del paisaje urbano crean una imagen nueva de la ciudad que destruye roles de género tradicionales y produce múltiples discursos de sexualidad. Durante la crisis de las agendas políticas que sucede en 1990-2000 los sujetos queer esbozan nuevos proyectos nacionales en cada isla. La familia como metáfora de la nación deja de basarse en los lazos de sangre, normas patriarcales y procreación biológica. En cambio, empieza a incorporar identidades raciales y prácticas sexuales. Yuxtaponiendo las narrativas de los tres países y poniendo en diálogos los temas de la nación, la sexualidad, el espacio urbano y el turismo sexual, Las ciudades del deseo rompe con una tradición que tiende a explorarlos por separado. El libro contribuye a una perspectiva nueva de la emergente cultura de resistencia contra las dinámicas heteronormativas y estructuras de poder que se está desarrollando simultáneamente en los tres países y establece conexiones extensas entre la literatura y el activismo LGBTQ en el Caribe hispano.